2009
DOI: 10.1007/s11739-009-0255-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of positive end-expiratory pressure on left ventricle diastolic function in healthy subjects

Abstract: We evaluated the acute effect of the application of positive end-expiratory pressure (PEEP) on LV diastolic function in 10 healthy subjects. We assessed load dependent diastolic function by Doppler examination of transmitral flow and load independent diastolic function by color M-mode propagation velocity of early flow into the LV cavity (Vp). During the application of PEEP in comparison to the baseline, we found a significant reduction of the E wave peak velocity [79 (64-83) vs. 65 (57-72) cm/s; p = 0.028] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…While these results are promising and suggest potential benefit for PEEP beyond respiratory support, other studies have not shown haemodynamic improvement with the use of PEEP 58 59. Of note, these authors found that PEEP was not associated with a functional decline in LV function at high levels of PEEP, and it was therefore considered safe in these group of patients.…”
Section: Invasive Ppv In Severe Systolic Heart Failurementioning
confidence: 89%
“…While these results are promising and suggest potential benefit for PEEP beyond respiratory support, other studies have not shown haemodynamic improvement with the use of PEEP 58 59. Of note, these authors found that PEEP was not associated with a functional decline in LV function at high levels of PEEP, and it was therefore considered safe in these group of patients.…”
Section: Invasive Ppv In Severe Systolic Heart Failurementioning
confidence: 89%
“…Many studies have demonstrated that alveolar recruitment manoeuvres (using high levels of PEEP) increase right ventricular afterload and decrease right ventricular preload, similarly to a Valsalva effect 9 . Moreover, augmented intrathoracic pressure induced by high level of PEEP, decreases right ventricle and increases left ventricle end—diastolic volume (EDV) as described also by transmitral pulsed-wave Doppler (PW-D) 10 . At the same time, PEEP decrease left ventricle afterload 11 .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Although anesthetics and positive end-expiratory pressure ventilation have been suggested to affect LA function and diastolic indices of the left ventricle, clinical studies in patients with underlying cardiac disease have shown conflicting results. [15][16][17][18][19][20] Given the growing prognostic value of atrial strain and diastolic function on perioperative outcomes after cardiac surgery, it is important to have a better understanding of the effects of general anesthesia (GA) and positive-pressure ventilation (PPV) on these indices in patients with cardiovascular disease. 8,14,[21][22][23] The primary aim of this study was to evaluate the effect of GA and PPV on LA mechanics, as measured by twodimensional speckle-tracking strain imaging, in patients undergoing cardiac surgery.…”
mentioning
confidence: 99%